Volume replacement with coconut water in rats with hemorrhagic shock - Farias, Domitila Costa de; Mariz, Juliana Câmara; Silva, Paula de Medeiros Nacácio; Medeiros, Vanessa de Fátima Lima Paiva; Macedo-Filho, Robson; Carvalho, Marília Daniela Ferreira de; Araújo-Filho, Irami; Rêgo, Amália Cínthia Meneses; Azevedo, Italo Medeiros de; Medeiros, Aldo da Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Purpose: Hemorrhagic shock+trauma is the third leading cause of death worldwide, supported by its frequency, severity and ability to induce systemic inflammatory responses and damage a number of organs. Currently, there is not an ideal fluid for volume replacement. There is relevant knowledge regarding the nutritional composition of coconut water (CW), but studies regarding its use for resuscitation in cases of hemorrhagic shock are lacking. The aim of this study is to evaluate the efficacy of modified coconut water (3% sodium) for resuscitation in hemorrhagic shock in an experimental model in rats. Methods: Wistar rats weighing 250-300g were used. In group 1 (n = 6) shock + coconut water (CW); group 2 (n=6) shock + fresh whole blood (FWB); group 3 (n = 6) shock+saline 0.9% (S). At the end of the experiment, levels of TNF, IL-1, IL-2, C-reactive Protein, AST, ALT, urea, creatinine were measured. Results: All animals survived the procedures and tests by the end of the experiment. There was a significant reduction in liver function tests (ALT and AST), urea and creatinine in animals treated with CW, compared with those treated with FWB and S (p <0, 05). However, no significant differences were observed when the parameters were compared between FWB and saline (p> 0.05) groups. The TNF-a, IL-1b and IL-2 expression were significantly lower in rats treated with CW than in rats treated with FWB and S (p <0.05). In animals treated with CW the mean level of C-reactive protein was lower than in saline rats (P <0.05). Conclusion: Our results demonstrate that, in rats with hemorrhagic shock, i.v. coconut water administration preserved renal and hepatic function, and was superior to fresh whole blood and saline with regard to proinflammatory cytokine expression.